Studi Pendahuluan Pengembangan Media Game Edukasi Spinnng Wheel Pada Perkembangan Bahasa Anak Kelompok B - Ulfa, Nasya; Gunawan, Gunawan; Astini, Baik Nilawati (Indonesian Journal of Elementary and Childhood Education, 2024)
This research aims to develop an effective "Spinning Wheel" educational game to enhance language development in Group B kindergarten children. Language development is a crucial aspect of early childhood growth, and the use of interactive game media is believed to be an engaging and effective approach. The research methodology employed is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results indicate that the "Spinning Wheel" educational game has been successfully developed and validated by media and content experts.